Analisis Strategi Pemasaran Online Pada CV. Artamas Konveksi Purwokerto - Widodo Wibisono; Mohammad Hidayatul Holili (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to find out the online marketing strategy implemented by CV. Artamas Konveksi Purwokerto. Data collection techniques are by means of scientific observation, interviews and documentation. The data analysis technique is carried out through data reduction, data presentation, and drawing conclusions. The research results stated that CV. Artamas Konveksi in its marketing strategy uses an electronic device called Gadged and uses social media Facebook, Instagram, Whatsapp, Shopee, Tik Tok and Snack video. It turns out that this online marketing strategy is able to expand marketing reach and increase sales turnover significantly.